Analisis Gen Blavim, Blandm dan Blaimp Carbapenemase dengan Alat Otomatis Vitek-2 dan Metode Polymerase Chain Reaction (PCR) pada Isolat Bakteri Enterobacteriaceae di RSUP Dr. Moh. Hoesin Palembang - Sabrina, Tia; Rivani, Erizka; Patricia, Venny (Sriwijaya Journal of Medicine, 2018)
Enterobacteriaceae is a normal flora in human intestinal tract which the most frequently caused the disease in human. Carbapenem is the last lines of antibiotic which used to treat severe infection that caused by gram-negative bacili bacteria, for example Enterobacteriaceae, but there is an increase prevalency of infection which caused by Carbapenem Resistant Enterobacteriaceae (CRE). The gene that encoding CRE is blaVIM, blaNDM, and blaIMP gene. The detection of these genes are very important to prevent spreading the nosocomial infection at hospital. The samples are from the speciment which has detected as isolate of Extended Spectrum Beta Lactamase (ESBL) Enterobacteriaceae bacteria and has occurred resistant to carbapenem group (meropenem and ertapenem) which detected by automatic equipment, VITEK 2 compact system. These samples will be processed by PCR with multiplex PCR technique to indentify blaVIM, blaNDM, and blaIMP gene. There are 43 samples consist of 33 samples (76,7%) ESBL bacteria isolate and 10 samples (23,3%) Carbapenemase bacteria isolate, 29 samples (67,4%) are Klebsiella pneumonia and 14 samples (32,6%) E. coli. These samples were from blood (5 samples/ 11,6%), sputum (16 samples/ 37,2%), peritoneal fluid (1 sample/ 2,3%), pus (4 samples/ 9,3%), urine (12 samples/ 28%), swab (3 samples/ 7%), tissue (1 sample/ 2,3%), and feces (1 sample/ 2,3%). From the PCR result, the gene was indentified from Enterobacteriaceae bacteria isolate was 28 samples (65,11%) from 43 samples. The indentified samples consist of 9 samples (32,1%) Carbapenemase bacteria isolate and 19 samples (67,9%) ESBL bacteria isolate. The identified of Enterobacteriaceae bacteria isolate consist of 15 samples blaNDM gene, 17 samples blaVIM gene, and 4 sample blaIMP gene.